Materials Science study aid on materials science for 15.03.01 mechanical engineering program - Khvorova, I. A. specialist in the field of materials science Senior Lecturer of Tomsk Polytechnic University 1954- (TPU Publishing House, 2012)
Scientific bases of the materials science, laws of metal and non-metallic constructional materials structure and properties formation are considered. The interrelation between structure and properties of materials is shown. Modern concepts of metals and alloys strengthening are given. Most widespread ferrous and nonferrous alloys are also considered. Short data on polymeric, ceramic and composite materials are cited. The study aid is designed at the Materials Science and Technology of Metals Department of the TPU. The manual is intended for training students majoring in the direction 150700 "Mechanical engineering".